Design Criteria of High Capacity Bus Transportation Systems - Caner, Cansu; Gür, Nazim Güneş; Gür, Nazim Güneş (Izmir Institute of Technology, 2005)
This thesis proposes to figure out a new model of public bus transportation mode in Turkey which is more competitive and effective among the conventional public transportation modes.In theoretical framework, the focus is on the new concepts and implementations developed in the urban transportation sector. The effective transportation systems regarding lower expenditures were handled according to the travel demands they serve.However, in general, the effectiveness of the modes is determined according to the economic parameters; mainly the conventional modes are discussed and the effectiveness of BRT systems and LRT systems are compared.A brief survey of the BRT (Bus Rapid Transportation) systems is handled to some extent. The design considerations and the results of the implemented examples are handled to constitute a guideline. The major public transportation modes of Izmir are handled to constitute a guideline. The major public transportation modes of Izmir are discussed. A reserved bus-transportation system is designed in the case study stage.Meanwhile the reserved bus concept along the Inönü Street is not designed according to the existing proposals. A distinctive model is concluded regarding the local conditions of Izmir. At final stage, the energy consumption rates of the systems are calculated and the economic comparison of the systems is based on this parameter.
Thesis (Master)--Izmir Institute of Technology, City and Regional Planning, Izmir, 2005
Includes bibliographical references
Text in English; Abstract: Turkish and English
xii, 109 leaves
Keywords: HE311.T9 .C21 2005; Urban transportation--Turkey--Izmir--Planning; City traffic--Turkey--Izmir